THE REFLECTION OF INFERIORITY COMPLEX IN THE SUN AND HER FLOWERS BY RUPI KAUR (Sastra Inggris UNPAM, 2022)
This thesis is entitled â€œThe Reflection of Inferiority Complex in The Sun and Her Flowers by Rupi Kaurâ€. The topic of this study is the inferiority complex. The object for this thesis is a book of the poem by Rupi Kaur entitled The Sun and Her Flowers (2017). The book tells about the speakerâ€™s life as an immigrant, about her family, love life, and society around her. The aim of this study is to analyze the speaker who suffer from an inferiority complex. In conducting this study, the writer used Alfred Adlerâ€™s theory in a book The Individual Psychology by Alfred Adler: A Systematic Presentation in Selection From His Writings (1956). And this thesis also used the qualitative method. The result showed that from the data analyzed it was found that the cause of the speakerâ€™s inferiority complex is the bad memories from childhood and during she grows up. The symptoms the speaker shows include anxiety, sorrow, despair, insecurity, and weakness.Keywords: adler, inferiority, poetry, rupi kaur